Conserved and species-specific chromatin remodeling and regulatory dynamics during mouse and chicken limb bud development - Shalu Jhanwar (Nature Portfolio, 2021)
The vertebrate limb bud is a paradigm to uncover the fundamental mechanisms that govern embryogenesis and evolutionary diversification. Here the authors compare mouse and chicken limb bud development to study the impact of genome evolution on conserved and divergent gene regulatory interactions.